Health at school - from instruction to development (Training and Practice : Journal of Educational Sciences, 2018)
Health-damages can be traced back to lifestyle and environmental factors. The definitions of tasks, however, are manifold. Although they can be defined as synonyms, it is worth differentiating one from the other.The instruction aims at orientating towards sustainable health conditions. It provides information both in direct and latent ways with the help of diversification of educational didactics. The development is an independent activity, improvement in the light of the knowledge of health resources, which can be carried out by developing the given organization with the help of health reflecting atmosphere as well as personal and material conditions. The schools of today, as an organization, have continuous tasks namely education of health (which is more than instruction) besides health improvement (which is more than health preservation and health education). The development is based on education – pedagogy which focuses on health force and encourages to choose health enhancing activities.